INSTITUSIONALISASI PARTAI POLITIK (Studi Pada Partai Demokrasi Indonesia Perjuangan) - Irma Rachmayani; Arizka Warganegara (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
This study aims to analyze the institutionalization process of the Indonesian Democratic Party of Struggle (PDIP). This study was designed using a descriptive qualitative research method. This method describes the research object based on existing and ongoing facts by collecting, understanding the chronological flow of events, and explaining the data obtained to then be analyzed according to existing theory. The research results show that: 1). The institutionalization of the PDIP party has not yet been actualized, seen through the domination of the party leader, namely Megawati Soekarnoputri. And the dominance of the political elite is still strong in giving birth to instant cadres. 2). The lack of clear ideology almost results in the absence of strong ties between political parties. There is almost no notable difference in terms of ideological lines between one political party and another. As a result of this, it was too easy for voters to move between their choices in each election according to the socio-political dynamics of the time. 3). The turnout rate of voters (voters turn out) continues to decline in every election. And 4). Another challenge for PDIP is public perception, until now PDIP can be assessed as a party that is still weak. This shows how weak the ideology that the party has built is still weak. The image of PDIP as the party is “little people”.